2012
DOI: 10.1007/s10047-012-0630-z
|View full text |Cite
|
Sign up to set email alerts
|

Eye-tracking analysis of skilled performance in clinical extracorporeal circulation

Abstract: The manipulation of extracorporeal circulation (ECC), which is performed by perfusionists during cardiovascular surgery, is a highly sophisticated cognitive process based on visual information obtained from information sources such as ECC indicators, surgeons, an operating field, a scrub nurse, surgical instruments, displays, patients, among others. An eye-tracking approach is expected to be a powerful means of automatic and rapid analysis. This paper presents the results of a pilot study in which an eye-track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
(10 reference statements)
2
19
0
Order By: Relevance
“…Only a few participants wrote comments, and they were not formally analyzed but included, ''having the glasses on did not change how I would have taken care of the patient,'' ''a little tight, however, they felt just like normal sunglasses,'' ''there could be more padding around the eyes,'' and ''once the simulation started, I was more concerned about the patient.'' The wearability reported by the participants is congruent with other studies actually done in the clinical setting (Koh et al, 2011;Tomizawa, Aoki, Suzuki, Matayoshi, & Yozu, 2012). Importantly, the technology has advanced tremendously since this study was completed with great improvements in comfort and wearability.…”
Section: Participant Feedbacksupporting
confidence: 75%
See 2 more Smart Citations
“…Only a few participants wrote comments, and they were not formally analyzed but included, ''having the glasses on did not change how I would have taken care of the patient,'' ''a little tight, however, they felt just like normal sunglasses,'' ''there could be more padding around the eyes,'' and ''once the simulation started, I was more concerned about the patient.'' The wearability reported by the participants is congruent with other studies actually done in the clinical setting (Koh et al, 2011;Tomizawa, Aoki, Suzuki, Matayoshi, & Yozu, 2012). Importantly, the technology has advanced tremendously since this study was completed with great improvements in comfort and wearability.…”
Section: Participant Feedbacksupporting
confidence: 75%
“…The ETG provided data that differentiated groups by substantial fixation differences in AOIs satisfying Aim 2. As in other studies (Koh et al, 2011;Matsumoto et al, 2011;Tomizawa et al, 2012), the scan path images and ETG data revealed a marked difference between how novices and experts are able to process data in a busy environment. While novices spent a significant amount of time looking at data that was not relevant to the ''patient's'' immediate problem (i.e., focusing on the heart rate of a dyspneic patient), the expert seemed to know what was important and was able to acquire the pertinent information much faster.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Regarding live surgeries, Atkins et al [3] and Tomizawa et al [37] studied expertise behavioural differences in the operating room (OR). Tomizawa et al reported that expert perfusionists tend to disperse their attention more widely than novices.…”
Section: Eye Tracking In Medical Trainingmentioning
confidence: 99%
“…In a study of operating room technicians utilizing circulation machines, eye-tracking revealed that expert technicians visually fixated upon a larger number of critical sources of information during the operative procedure as compared to novices (Y. Tomizawa et al, 2012). With knowledge of these differences, it may be possible to incorporate eye-tracking as a component of self-assessment in early medical practice.…”
Section: Constraints Of Eye-tracking Experimentsmentioning
confidence: 99%